2019
DOI: 10.1002/elan.201800773
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Architecture of Modified Carbon Nanotubes/Electrochemically Reduced Graphene Oxide Nanomaterial for Fast Electron Transfer. Application in Glucose Biosensor

Abstract: Electron transfer (ET) reactions in bioelectrocatalysis of enzymes at electrode surfaces require not only the efficient immobilization, but also highly conductive nanostructured platform, which allows for retaining its bioactivity and structural conformation. The novel architecture of spatially separated electrochemically reduced graphene oxide (ERGO) by multi‐walled carbon nanotubes functionalized with 4‐(pyrrole‐1‐yl) benzoic acid (MWCNT/PyBA) with the accurate porous structure could be an alternative for ea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 42 publications
(118 reference statements)
0
2
0
Order By: Relevance
“…Oxygen as a natural redox mediator normally exist in the test solutions. 25 The oxygen-based biosensors are known as the firstgeneration biosensors. 26 The mechanism of signal production in O 2 -mediator biosensors can be described as follows: 19 Glucose GOx FAD gluconolactone GOx FADH…”
Section: Resultsmentioning
confidence: 99%
“…Oxygen as a natural redox mediator normally exist in the test solutions. 25 The oxygen-based biosensors are known as the firstgeneration biosensors. 26 The mechanism of signal production in O 2 -mediator biosensors can be described as follows: 19 Glucose GOx FAD gluconolactone GOx FADH…”
Section: Resultsmentioning
confidence: 99%
“…Through CV experiments, it was reported that the presence of ERGO in the conductive material increase the rate of electron transfer between the enzyme redox centre and the electrode surface. 362 Detection of DNA.-The detection of DNA plays a pivotal role in the diagnosis of various genetic or mutated medical ailments in the body. The electrochemical biosensor employed for detection of DNA has attracted the attention of researchers due to its low cost, high sensitivity and high selectivity for the detection of DNA sequences or mutated genes responsible for the various human diseases.…”
Section: Graphene Based Electrochemical Biosensorsmentioning
confidence: 99%